A Combined Surgical Approach for Extensor Hallucis Longus Reconstruction: Two Case Reports - Duarte, Marta; Fradinho, Nuno (Indian Journal of Plastic Surgery, 2020)
The surgical management of foot tendon injuries is not well-represented in literature. To achieve excellent functional recovery of the extensor hallucis longus (EHL) tendon, we aimed at developing a reliable and feasible reconstructive technique.A surgical technique for delayed reconstruction of the EHL tendon, combining an elongation procedure with second toe extensor tendon transfer, is described in this article.The results of this combined approach for EHL tendon reconstruction were remarkable, since the patients of the two clinical cases reported regained active extension of the hallux after 6 months without any associated complication.This study represents a step forward in foot surgery, since it describes an alternative technique to manage EHL tendon lesions.
Keywords: extensor hallucis longus; tendon; reconstruction